Participação das proteínas ezrina, radixina e moesina (ERM proteins) na invasão celular por amastigotas extracelulares de Trypanosoma cruzi - Ferreira, Éden Ramalho de Araujo [UNIFESP] (2016)
The protozoan parasite Trypanosoma cruzi is the causative agent of Chagas? disease that affects 6-7 million people worldwide, mostly in the South and Central America. Chagas? disease was responsible for 76% of all deaths caused by Neglected Tropical Diseases in Brazil from 2000 to 2011. In mammalian hosts T. cruzi alternates from extracellular (infective) trypomastigote forms and intracellular (replicative) amastigote forms. Additionally, trypomastigotes can differentiate into amastigotes in the extracellular environment generating infective extracellular amastigotes (EAs). Host cell invasion by these forms is mediated by complex cellular signaling events regulating actin filaments, the main component in EA uptake. ERM proteins (ezrin, radixin and moesin) are key elements linking actin filaments to the plasma membrane, important for the maintenance of cell morphology, cell migration and invasion of intracellular pathogens. The aim of this study was to evaluate the role of ERM proteins in actin cytoskeleton-plasma membrane interplay during host cell invasion by EAs. Our results revealed that depletion of host ezrin and radixin but not moesin inhibited EAs invasion in HeLa cells. Confocal microscopy of HeLa cells transfected with ERM proteins?GFP or -HA revealed recruitment of ERM proteins to EAs invasion sites colocalizing with F-actin. Additionally, invasion assays performed with cells overexpressing ERM proteins revealed increased EAs invasion in ezrin and radixin but not moesin overexpressing cells. Finally, time-lapse live imaging confocal microscopy has shown reduced and delayed actin dynamics in ezrin and radixin depleted HeLa cells when compared to control or moesin groups. Altogether, these findings show distinct roles of ERM proteins in actin filament dynamics and plasma membrane interplay during EAs host cell invasion.